Gabriel graph of geomagnetic Sq variations - Sridharan, M.; Ramasamy, Ayyathurai M.S. (My University, 2010)
This paper describes the pattern of geomagnetic solar quiet day, Sq, variations recorded at the Indian geomagnetic observatories. The extent to which the high and low latitude ionosphere is interlinked electromagnetically during periods of quiet geomagnetic conditions is a point of debate. The concept of Gabriel graph is applied to derive the boundaries for the variations of horizontal, vertical, and declination components of the earth’s magnetic field during geomagnetically quiet periods. Data of the six Indian geomagnetic observatories (Alibag, Hyderabad, Nagpur, Pondicherry, Visakapatnam, and Trivandrum) are considered for this analysis. This graph theoretical model is complementary to the classical data analysis techniques. Analytical method and the results of the analysis are presented in the paper.
Keywords: Geomagnetic Sq variation; Gabriel graph; Euclidean distance; Earth’s magnetic field; Sq variation